SYNTHESIS OF 6-EPICASTANOSPERMINE AND 1,6-DIEPICASTANOSPERMINE FROM L-GULONOLACTONE AND SYNTHESIS OF L-6-EPICASTANOSPERMINE AND L-1,6-DIEPICASTANOSPERMINE FROM D-GULONOLACTONE - Fleet, G; Ramsden, N; Molyneux, R; Jacob, G (1988)
The syntheses of the natural product 6-epicastanospermine [(1S,6R,7R,8R,8aR)-1,6,7,8-tetrahydroxyoctahydroindolizine], isolated from Castanospermum australe, and of 1,6-diepicastanospermine [(1R,6R,7R,8R,8aR)-1,6,7,8-tetrahydroxyoctahydro-indolizine] from L-gulonolactone and the synthesis of the enantiomers, L-6-epicastanospermine [(1R,6S,7S,8S,8aS)-1,6,7,8-tetrahydroxyoctahydroindolizine] and L-1,6-diepicastanospermine [(1S,6S,7S,8S,8aS)-1,6,7,8-tetrahydroxyoctahydro-indolizine] from D-gulonolactone are reported. © 1988.